ATHLETES PREPARING TO COMPETE COACH - TEACHER-INNOVATIVE APPROACH - Usmonov Ne’matullo (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
regular athletes to achieve success in sports competitions in the improvement of general and special members sports a guarantee of achievement prep is going. Trenirovka intertwined with the process of sports training tools and the improvement of the periodic stages. Athletes preparing to compete in the article coach - the function of the teacher, the issue of introduction of innovative technologies studied.